«Те, що не припиняє не писатися»: лаканівська призматика еротики в текстах Миколи Хвильового - Куценко, Марина; Kutsenko, Marina (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті вміщено інтерпретацію еротичного дискурсу Миколи Хвильового в аспекті структурного психоаналізу. Утверджується думка, що, попри насиченість творчості письменника еротичними елементами, інтимні стосунки чоловіка й жінки в ній постають невдалими, неможливими, відсутніми, що зумовлюється нарцисичною природою любові й мовним бар’єром. Особливу увагу в розвідці приділено взаємозв’язку Еросу й письма. The article offers an analysis of erotic discourse in Mykola Khvylovy’s texts within structural psychoanalysis. It argues that erotica in the prose of Khvylovy appears to be a writing about the absence of sexual relationships and love, some initial impossibility, that has been caused by several factors: the narcissistic nature of love (Eros is regarded as a way of the imaginary reconstruction of Ego by the «split subject»), the difference between male and female enjoyment and the presence of language barrier. The heroes of Khvylovy are focused primarily on their own inherent contradictions, so they either deny love or try to harmonize their inner world with its help. Such heroes deal not with the object of love (man or woman), but with fantasmatic object of desire that their imagination puts in the Other. Also love in Khvylovy’s texts is regarded as a desire for union with the Absolute, as a need for motherhood and as a linguistic failure. Special attention is paid to the interrelation between Eros and writing.
«That Which Never Ceases Not Being Written»: Lacanian Reading of Erotica in Mykola Khvylovy’s Texts
Keywords: Ерос; Одне (Un); «об’єкта»; «надлишкова насолода»; означник; Eros; One (Un); «object a»; «excessive pleasure»; signifier